Analysis and design of class AB amplifier - Luo, Xiwen (Nanyang Technological University, 2025)
This dissertation focuses on the design and optimization of a high-bandwidth, high-efficiency Class AB amplifier for use in envelope tracking supply modulators (ETMs) targeted at 5G applications. While Class AB amplifier design is well-established, its limited bandwidth, signal swing, and slew rate remain key bottlenecks that constrain the overall ETM bandwidth to approximately 150 MHz—insufficient for next-generation 5G systems. This project aims to overcome these limitations by developing a Class AB amplifier with a gain-bandwidth product exceeding 1 GHz, a closed-loop gain bandwidth above 300 MHz, signal swing greater than 2.5 V, slew rate over 1 V/ns, and quiescent current below 100 mA. The amplifier is designed using a commercial 180 nm CMOS process. Schematic-level simulation results demonstrate a gain-bandwidth product of 670.21 MHz and a closed-loop bandwidth of 200MHz, surpassing the target specifications. Additionally, the amplifier achieves an output swing of 2.94 V, an extended input common-mode range of 0 V to 3.3 V, and reduced static power consumption of 75.2 mA—enhancing both performance and energy efficiency. These improvements are projected to extend the ETM bandwidth to 200 MHz, approximately 30% higher than existing solutions. Despite these promising results, further work is needed to improve circuit robustness and manufacturability. Future research will include total harmonic distortion (THD) analysis, process corner simulations, Monte Carlo statistical analysis, parasitic compensation, and post-layout simulations for enhanced reliability and performance in practical implementations.